Molecular Identification of a Moricin Family Antimicrobial Peptide (Px-Mor) From Plutella xylostella With Activities Against the Opportunistic Human Pathogen Aureobasidium pullulans - Xu, Xiaoxia; Zhong, Anqiao; Wang, Yansheng; Lin, Boda; Li, Peng; Ju, Wenyan; Zhu, Xiaojia; Yu, Jing; De Mandal, Surajit; Jin, Fengliang (Frontiers in Microbiology, 2019)
Antimicrobial peptides (AMPs) represent the largest group of endogenous compounds and serves as a novel alternative to traditional antibiotics for the treatment of pathogenic microorganisms. Moricin is an important α-helical AMP plays a crucial role in insect humoral defense reactions. The present study was designed to identify and characterize novel AMP moricin (Px-Mor) from diamondback moth (Plutella xylostella) and tested its activity against bacterial and fungal infection including the opportunistic human pathogen Aureobasidium pullulans. Molecular cloning of Px-Mor using rapid amplification of cDNA ends revealed a 482 bp full length cDNA with 198 bp coding region. The deduced protein sequence contained 65 amino acids, and the mature peptides contained 42 amino acid residues with a molecular mass of 4.393 kDa. Expression analysis revealed that Px-Mor was expressed throughout the life cycle of P. xylostella with the highest level detectable in the fourth instar and prepupa stage. Tissue specific distribution showed that Px-Mor was highly expressed in fat body and hemocyte. In vitro, antimicrobial assays indicated that Px-Mor exhibited a broad antimicrobial spectrum against Gram positive bacteria (GPB), Gram negative bacteria (GNB) and fungi. Moreover, scanning electron microscopy and transmission electron microscopy (TEM) revealed that Px-Mor can cause obvious morphological alterations in A. pullulans, which demonstrated its powerful effect on the mycelia growth inhibition. Taken together, these results indicate that Px-Mor plays an important role in the immune responses of P. xylostella and can be further exploited as an antimicrobial agent against various diseases including for the treatment of A. pullulans infection.